46 Young at heart: risk factor assessment of young adults (≤45) with st elevated myocardial infarction. (16th October 2019) - Kumar, R; Kumar, J; O'Connor, C; Sankhyan, N; Malik, I; Shakoor, MN; Zaman, J; Turner, E; Buckley, A; Maloney, A; Arnous, S; Kiernan, T
Abstract : Introduction: Premature cardiovascular disease (defined by a cardiovascular end-point at <45 years of age) is becoming increasingly common. It is believed increasingly dietary changes and inactive lifestyle play a significant role in its pathogenesis. Limited studies have been performed on patients presenting with ST segment Elevation Myocardial Infarction (STEMI) under the age of 45. The aim of this study was to compare the risk factors, clinical characteristics, laboratory investigation, angiographic features and outcomes of patients <45 years presenting with STEMI. Methods: This study is a single-center retrospective observational study involving patients ≤45 years presenting with STEMI between January 2012 and December 2018. Patient data was collected by chart review, electronic health record and telephone conversation. Standard Bayesian statistics were employed for analysis. Results: 1463 patients presented as STEMI during the study duration. Patients aged ≤45 comprised 7.6% (n=113) of the total patients presenting with STEMI. The vast majority of patients in this age category were male (93/113, 82.3%). Anterior STEMI was the most common presentation, and thus the left anterior descending artery (LAD) was the most common infarct-related artery (IRA).Regarding risk factors for cardiovascular disease, 35% had a background of hypertension, 9.7% had HBA1c levels over 42 mmol/mol, and 50% had a positive smoking history. 93.1% of patients were not previously on any medications, and STEMI as their first presentation to the healthcare system. Presenting LDL, HDL, total cholesterol and average triglyceride levels were measured at an average of 3.10 mmol/L, 1.03 mmol/L, 4.81 mmol/L, and 1.86 mmol/L respectively. Conclusion: Our study correlates with previous literature suggesting that modifiable risk factors are-lesser-so associated with premature onset of CAD. Risk factors such as family history and hereditary variants play a greater role in the development of premature CAD. 93.1% of patients were not previously on any medications, and STEMI as their first presentation to the healthcare system. This suggests a need for greater awareness of genetic predisposition of cardiovascular disease on a population-level, and need for early referral of high-risk individuals to specialist services.